Thermal Conductivity of Compressed Stabilized Earth Brick (CSEB) Different Rate Percentage of Binder Use - Karsono, Darnarti; Yuuwono, Abito Bamban; Kurniawan DS, Kukuh (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2020)
Abstract. The level of conductivity of building skin material is one of the factors that influence the thermal conditions of a space, compressed stabilized earth bricks are proven to be more economical, environmentally friendly, stronger and have better ability to withstand the rate of heat propagation compared to ordinary firebrick , the number of percentages of the use of binder (binder) on bricks without burning will affect the level of thermal conductivity, in this article we test bricks without fires with the level of the number of percentages of use of different binder materials, bricks without fires with a smaller percentage of binder material / a little will have a slower rate of heat conductivity (better) and the higher the percentage of the use of binder material, the level of heat conductivity will be faster (not Good).Keywords: conductivity, thermal, brick without burning, Binder